1977
DOI: 10.1203/00006450-197704000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Energy Metabolism of Brain in Human Protein-Calorie Malnutrition

Abstract: SummaryCerebral blood flow (CBF) and carbohydrate metabolism were studied in 5 normal children and 25 children, aged 40 months or less, with varying degrees of protein-calorie malnutrition (PCM). CBF in normal children and those suffering from grade I PCM was 90.3 * 5.7 mVlOO glmin, a value comparable with that obtained by other investigators, but the proportion of glucose taken up by the brain which combined with oxygen, the oxygen/glucose index (OGI), was 65.8%, indicating significant conversion of glucose i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

1980
1980
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 7 publications
0
15
1
Order By: Relevance
“…In severe human PCM (marasmus), oxygen consumption is diminished (16). Recently, it has also been observed that a similar situation exists for the brain (17). It is thus possible that the constraint of oxygen consumption affects the process of acetylation as well.…”
Section: Discussionmentioning
confidence: 84%
“…In severe human PCM (marasmus), oxygen consumption is diminished (16). Recently, it has also been observed that a similar situation exists for the brain (17). It is thus possible that the constraint of oxygen consumption affects the process of acetylation as well.…”
Section: Discussionmentioning
confidence: 84%
“…This is in part the consequence of lack of easy accessibility of this organ for such studies. Previous studies have quanti®ed oxygen and glucose consumption by the brain in anesthetized or unanesthetized children using Fick's principle (Settergren et al, 1976(Settergren et al, , 1980Mehta et al, 1977;Kennedy & Sokoloff, 1957;Kennedy, 1956;Sokoloff et al, 1977). Arterio-venous gradients of glucose, oxygen, lactate, pyruvate and ketones were measured across the brain.…”
Section: Response To Administration Of Glucosementioning
confidence: 99%
“…It should be underscored that such computation assumes that oxidation is the only fate of cerebral glucose uptake, and that glucose is the only oxidative fuel being utilized by the brain. The last two assumptions are appropriate, considering that the contribution of ketones, except in prolonged fasting in adults, is small and that non-oxidative disposal of glucose, that is, release of lactate and pyruvate by the brain, is also small (Settergren et al 1976(Settergren et al , 1980Mehta et al, 1977). Recently, cerebral metabolic rate of glucose has been quanti®ed in children and adults using positron emission tomography (PET).…”
Section: Response To Administration Of Glucosementioning
confidence: 99%
“…We, therefore, wondered whether in some patients, besides glucose, lactate might be utilized as an energy substrate by the brain and thus protect the child against the deleterious effects of glucose depletion. This would be opposite to the situation in normal children (18,22,24,25,26) and normal adults (4, 9, 23), in whom the brain releases lactate and consumes ketone bodies (P-OHB and AcAc) as soon as glucose, the preferential fuel, becomes insufficiently available. In G6Pase-deficient children, however, this is impossible because there is no physiologic hyperketosis during fasting.…”
mentioning
confidence: 58%